Ronald Reagan, Governor, California [speech], 1972 (1972)
[00:00:00] Random chatting [00:00:28] Long applause [00:01:00] Introduction of various California officials [00:01:40] Introduction of Gov. Ronald Reagan [00:02:30] Reagan speaks about reforming the California government and economic progress [00:03:22] Reagan says urgent need to reduce size of government [00:04:04] Reagan addresses problems of education, environmental, taxation, and industrial employment concerns [00:05:00] Reagan states that Space Shuttle program was approved to happen in California, along with new defense contract with the Federal Government [00:06:20] Reagan talks about increased benefits for workers and unemployed along with what businesses and government can do to improve them [00:07:20] Reagan talks about California Agricultural industry and union choices [00:08:15] Reagan talks about reformed welfare program and higher restrictions [00:10:00] Reagan wants to develop a system for medical care in California, doing research [00:11:55] Reagan talks about tackling the venereal disease problem in cal. [00:12:55] Reagan talks about consumer protection [00:14:15] Reagan talks about reforming public education property tax funding to ease cost on homeowners and other education reforms he plans to achieve [00:19:30] Reagan talks about various tax reforms that have been enacted [00:20:40] Reagan talks about increase in salaries and correcting salary inequities for employees in the CSU system [00:21:41] Reagan wants to submit the budget in two sections to increase understanding of the budget [00:22:50] Reagan talks about prison reforms and successes in the California Corrections system [00:23:45] Reagan wants to correct violence issue in prisons and eventually close San Quentin Prison [00:25:10] Reagan talks about creating local law enforcement training academies [00:25:52] Reagan talks about drug trade and drug treatment programs [00:26:20] Reagan talks about success in lowering traffic fatalities and collision [00:27:09] Reagan wants to develop a department of transportation [00:27:17] Reagan says thanks for passing air quality control act and other environmental protection programs [00:28:45] Reagan begins to end speech [00:30:30] Applause